Tsunami at Haeundae - Youn, JK; Hwi, Kim (Korea : CJ Entertaiment, 2009)
The Indian ocean tsunami at 2004 was the worst tsunami recorded in history with many lives lost. Man Sik experienced the disaster, when he and his man got stranded mid-sea while deep-sea fishing. A marine geologist Kin Hwi discovers that the sea is showing signs of activity similar to the Indian Ocean at the time of the 2004 Tsunami and heads down to Haeundae to warn authority
Title from container
cast : Sul Kyung Gu, Ha Ji-Won, Park Joong-Hoon, Uhm Jung-Hwa
DVD format
Keywords: Tsunamis -- Korea (South) -- Drama; Man-woman relationships -- Korea (South) -- Drama; Love stories, Korean; Feature films